2017
DOI: 10.14348/molcells.2017.2207
|View full text |Cite
|
Sign up to set email alerts
|

The Integrins Involved in Soybean Agglutinin-Induced Cell Cycle Alterations in IPEC-J2

Abstract: Soybean agglutinin (SBA) is an anti-nutritional factor of soybean, affecting cell proliferation and inducing cytotoxicity. Integrins are transmembrane receptors, mediating a variety of cell biological processes. This research aims to study the effects of SBA on cell proliferation and cell cycle progression of the intestinal epithelial cell line from piglets (IPEC-J2), to identify the integrin subunits especially expressed in IPEC-J2s, and to analyze the functions of these integrins on IPEC-J2 cell cycle progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 35 publications
0
31
1
Order By: Relevance
“…In addition, Schierack et al, (2006) reported an increased in the proliferation of IPEC-J2 cells after exposure to different Escherichia coli strains. Contrary to our findings, Pan et al (2013Pan et al ( , 2017 observed a decrease in the cell proliferation rate after treatment of IPEC-J2 cells with soybean agglutinin. In addition, Yoou, Kim, and Jeong (2015) reported that acteoside decreases the proliferation of thymic stromal lymphopoietin (TSLP)stimulated human mast cells.…”
Section: Ipec-j2 Cell Proliferationcontrasting
confidence: 99%
See 3 more Smart Citations
“…In addition, Schierack et al, (2006) reported an increased in the proliferation of IPEC-J2 cells after exposure to different Escherichia coli strains. Contrary to our findings, Pan et al (2013Pan et al ( , 2017 observed a decrease in the cell proliferation rate after treatment of IPEC-J2 cells with soybean agglutinin. In addition, Yoou, Kim, and Jeong (2015) reported that acteoside decreases the proliferation of thymic stromal lymphopoietin (TSLP)stimulated human mast cells.…”
Section: Ipec-j2 Cell Proliferationcontrasting
confidence: 99%
“…The occurrence of antibiotic‐resistant strains among many pathogenic microorganisms and consumer requirement for organic food products has triggered the search for an alternative approach to control microbial infection in pigs (Adams et al, ; Che et al, ). The supplementation of various plant extracts in animal studies or in vitro studies has served as a promising alternative to antibiotic use (Che et al, ; Pan et al, ; Wang et al, ; Zhao et al, ). Understanding how these plant extracts modify the gastrointestinal milieus and nutritional requirements of pigs (Skjolaas, Burkey, Dritz, & Minton, ) and other animals is vital.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The release of alkaline phosphatase in the intestinal epithelial cells increases intestinal membrane permeability, elevating the occurrence of inflammation and infections (Bates, Akerlund, Mittge, & Guillemin, ; Geddes & Philpott, ), and decrease in TEER value. The increase in intestinal membrane permeability results in the reduction in tight junction integrity, disruption of cell‐to‐cell adhesions and decrease in cell viability and causes intestinal villus atrophy (Grant, Ewen et al, ; Pan et al, ; Pan, Zhao et al, ; Zhao et al, ), affecting cellular morphology, metabolism and proliferation (Pan et al, ). Several studies reported that the supplementation of SBA in intestinal epithelial cells decreased the TEER value, hence affecting membrane permeability (Dalla Pellegrina et al, ,; Pan et al, ).…”
Section: Discussionmentioning
confidence: 99%